Leader’s sensegiving and promotion of team sensemaking: Two sides of the same coin - Passos, A. M.; Sinval, J.; Sousa Guedes, A.; Santos,C.M.; Uitdewilligen, S. (14th INGRoup Annual Conference, 2019)
The authors differentiate two leadership functions related to sensemaking: leader’s sensegiving and leader’s promotion of team sensemaking. Results from two field studies validate the two constructs and indicate that the influence of leader’s sensegiving on team performance is higher in situations that leaders also promote team sensemaking.